The Influence Of Location, Price, Service On The Decision To Purchase Refilled Drinking Water NN RO Bengkulu - Miswan Basrudin Bondar; Ermy Wijaya; Iswidana Utama Putra (Penerbit Jurnal Indonesia, 2023)
The aim of this research is to determine the influence of location, price and service on the decision to purchase NN RO Bengkulu refillable drinking water. . The data collection method in this research used observation techniques and questionnaires, with a sample of 110 respondents. The research results show that the results of multiple linear regression show Y = 20.354 + 0.230 (X1) + 0.268 (X2) + 0.123 (X3) + 3.696. This illustrates a positive regression direction, meaning that there is a significant influence between the variables location (X1) price (X2) and service (X3) on purchasing decisions (Y) for NN RO Bengkulu refillable drinking water. From the results of the t test for the location variable (X1), it shows that tcount is 3,045 > ttable 1,658 and the significance is 0.003 < 0.05, meaning that location (X1) has a positive and significant effect on purchasing decisions (Y) for NN RO Bengkulu refillable drinking water. The price test results (X2) show tcount 4,112 > ttable 1,658 and significance 0.000 < 0.05, meaning that price (X2) has a positive and significant effect on purchasing decisions (Y) for NN RO Bengkulu refillable drinking water. The results of the service test (X3) show tcount 2,855 > ttable 1,658 and significance 0.005 < 0.05, meaning that service (X3) has a positive and significant effect on purchasing decisions (Y) for NN RO Bengkulu refillable drinking water.